Transcriptome Profiling Unveils the Mechanisms of Inflammation, Apoptosis, and Fibrosis in the Liver of Juvenile Largemouth Bass Micropterus salmoides Fed High-Starch Diets - Xifeng Liu; Hongkang Liu; Kangwei Wang; Chuanjie Qin; Yuanfa He; Li Luo; Shimei Lin; Yongjun Chen (Animals)
The aim of this study was to explain the mechanism underlying the liver injury of juvenile largemouth bass Micropterus salmoides in response to high-starch diet intake. Three diets were formulated with different starch levels, being abbreviated as treatment LS (low starch, 8.13% starch), MS (medium starch, 14.1% starch), and HS (high starch, 20.1% starch), respectively. Fish were fed with their respective diets to apparent satiation for 56 days. The results showed that growth retardation of the HS fish was associated with the reduction in feed intake rather than feed utilization. Histological evaluation of the livers showed that vacuolization was the most prevalent characteristic in the MS fish, while ballooning degeneration, apoptosis, fibrosis, and inflammation were observed in the HS fish. Transcriptome profiling suggested that liver inflammation was mediated by Tlr signal transduction, which activated the Pi3k/Akt/Nfκb signaling axis to promote the release of proinflammatory factors including Il-8 and Ip-10. Hepatocyte apoptosis was mediated by the extrinsic pathway through death receptors including Fas and Tnfr, which coordinately activated the Fadd/caspase-8 death signaling axis. An autonomous inhibition program was identified to counteract the apoptosis signal, and the PI3K/Akt signaling pathway might play an important role in this process through regulating the expression of iap and diablo. Liver fibrosis was mediated through the Tgf-β and Hh signaling pathways. Upon secretion, Tgf-β1/3 bound to TgfβrI/II complex on the liver cell membrane, which induced the phosphorylation of downstream Smad2/3. When Hh interacted with the membrane receptor Ptc, Smo was activated to initiate signaling, driving the activation of Gli. The activation of both Smad2/3 and Gli promoted their nuclear translocation thereby regulating the transcription of target genes, which resulted in the activation and proliferation of HSCs. The activated HSCs constantly expressed colla1 and ctgf, which facilitated substantial accumulation of ECM. It should be noted that the molecular mechanism of liver injury in this study was speculated from the transcriptome data thus further experimental verification is warranted for this speculation.